(untitled) (Biological Sciences - PJSIR, 2022)
Lead oral exposure related pathological changes in kidneys and their ameliorations through Jambul Fruit Pulp Extract (JFPE) treatment were investigated in Albino Laboratory Mice. Adult male animals (n=30) weighing an average of 30 g were equally distributed into three groups, control (no treatment), lead (Pb) group (50 ppm Pb ions from lead acetate were given in drinking water 15 days+Pb ions free water 5 days) and Pb-J (lead+Jambul) group (50 ppm Pb ions as in Pb group+Jambul pulp extract 0.2 mL from 16-20 days). All animals were euthanized to recover kidneys for histopathological study on day 21. Results showed Pb exposure related significant decline in kidney and animal body weights. Histopathological findings were shrinkage of glomeruli and the proximal tubules, whereas the micrometric data indicated significant decline in glomerular size (2233.91±47.9 µm2) CSA (cross sectional area) of tubule size (561.0±23.4 µm2), caliber (97.9±7.2 µ2), wall thickness (462.0±22.8 µ2) and number of glomeruli per unit area (1.56±0.2) in Pb group. All these weight parameters, histopathological signs and micrometric observations indicate very good signs of recovery from such pathological changes in Pb-J group. These findings clearly show the importance of JFPE towards rehabilitation of the functional micro-architecture of the kidneys after Pb ion exposure related damage.